PENGARUH KEBIJAKAN MONETER TERHADAP PERTUMBUHAN EKONOMI - Budiyanto, Very; Wibowo, Wisnu (2021)
This study investigates the effect of monetary policy on economic growth in Indonesia. Gross Domestic Product (GDP) is used as the dependent variable on the explanatory variables of monetary policy: inflation, money supply (M2), exchange rates and interest rates”.Time series data are from 1986 to 2019. This study adopts the Ordinary Least Squared (OLS) technique.”The results showed that inflation has a significant and negative effect on economic growth in Indonesia, the money supply (M2) and the exchange rate are significant variables affecting economic growth in Indonesia”. Meanwhile, interest rates do not have a significant and negative effect on economic growth in Indonesia